Molecular characterization of a short neuropeptide F signaling system in the swimming crab, Portunus trituberculatus, and its role in ovarian development - Zhou, Qi; Li, Xiafei; Shen, Xiquan; Zhu, Dongfa; Xie, Xi (Frontiers in Marine Science, 2024)
Short neuropeptide F (sNPF) is a neuropeptide that widely distributed among arthropods. This neuropeptide has been proposed to play pleiotropic roles in insects, but its physiological functions in crustaceans are poorly understood. Here, we cloned the cDNA sequences of sNPF and its putative receptor (sNPFR) from the swimming crab, Portunus trituberculatus, and determined their possible roles during ovarian development. PtsNPF encodes three sNPF mature peptides with a conserved C-terminal “RLRFG” motif. All three PtsNPF peptides concentration-dependently activated PtsNPFR expressed in HEK293T cells, with EC50 values in the nanomolar range. PtsNPF and PtsNPFR transcripts showed a broad distribution among neural and non-neural tissues. During the ovarian development, expression of PtsNPF and PtsNPFR in hepatopancreas and ovary both increased to the highest levels at the late-vitellogenic stage, a period for rapid vitellogenesis. The in vitro experiments further showed that, among the three sNPF peptides, sNPF3 treatments can induce the vitellogenin (Vg) gene and protein levels in the hepatopancreas, as well as the Vg receptor (VgR) gene and protein levels and vitellogenin (Vn) deposition in the ovary. Opposing effects were observed for the dsPtsNPFR treatments, suggesting that PtsNPFR plays a role in the PtsNPF-mediated vitellogenesis. Additionally, it was found that the PtsNPF/PtsNPFR system can activate different second messengers species in hepatopancreas and ovary, suggesting it may act via different G proteins.